Synthesis of renewable isoindolines from bio-based furfurals - Xu, Feng; Li, Zao; Zhang, Li-Long; Liu, Shengqi; Li, Hu; Liao, Yuhe; Yang, Song (Green chemistry : an international journal and green chemistry resource : GC, 2023)
Upgrading biomass-derived platforms to functionalized aromatics by a tandem Diels-Alder (DA) cycloaddition-aromatization strategy has attracted broad attention. However, three challenges exist: improving the equilibrium of DA cycloaddition, controlling the regioselectivity of DA adducts, and increasing the stability of the cycloadduct. Herein, an intramolecular cycloaromatization strategy was developed for the direct upgradation of bio-furfurals to isoindolinones under liquid phase conditions via the selective formation of exo -DA adducts. The efficiency of the intramolecular DA cycloaddition was remarkably promoted by a defective Zn-BTC-SA catalyst quantitatively forming the desired regioselective exo -DA cycloadduct with higher thermal stability. Meanwhile, the co-existence of an acidic ionic liquid ([Hmim]HSO 4 ) could facilitate the subsequent aromatization to generate isoindolinones in quantitative yields. Theoretical calculations elaborated the significance of the in situ formed exo -DA adducts with enhanced stability in the cascade conversion process. Moreover, this protocol is applicable to the production of a wide range of renewable isoindolinone derivatives and commercial medicines in excellent yields (>92%) and is suitable for gram-scale reactions. Sugar aromatization: the efficient conversion of bio-furanics to versatile renewable isoindolinones is achieved by a self-stabilized cycloaromatization strategy.